The Influence of Information Technology Usage on Students' Learning Outcomes in Islamic Religious Education (PAI) - Niken Hafizah; Sirajul Januardi (Formad English Foundation NTB Jakarta, 2025)
The rapid advancement of information technology has significantly influenced various aspects of education, including Islamic Religious Education (PAI). This study investigates the impact of information technology usage on students' learning outcomes in PAI through a systematic literature review. Relevant academic sources from reputable databases were analyzed to identify common themes and gaps in existing research. The findings indicate that integrating information technology into PAI instruction enhances teaching strategies, student engagement, and academic performance. Digital tools such as online platforms, interactive applications, and video conferencing facilitate flexible and accessible learning, fostering active student participation. Additionally, structured assessment methods and independent learning play crucial roles in improving students' comprehension and retention of PAI materials. Despite these advantages, challenges such as technological accessibility, teacher competence, and digital literacy persist. Addressing these challenges requires strategic policies and targeted teacher training programs to maximize the effectiveness of information technology in PAI education. Future research should explore practical solutions to overcome these barriers and further optimize digital learning strategies in religious education.